Confocal laser endomicroscopy in head and neck malignancies using FITC‐labelled EpCAM‐ and EGF‐R‐antibodies in cell lines and tumor biopsies. Issue 10 (20th January 2017) - Englhard, Anna S.; Palaras, Alexander; Volgger, Veronika; Stepp, Herbert; Mack, Brigitte; Libl, Darko; Gires, Olivier; Betz, Christian S.
Abstract : Intraoperative detection of residual malignant cells at tumor margins following excision of primary tumors could help improving surgery and thus patients' outcome. The feasibility of the tumor antigens epidermal growth factor receptor (EGF‐R) and epithelial cell adhesion molecule (EpCAM) for antibody‐dependent confocal laser scanning endomicroscopy (CLE)‐mediated visualization of malignant cells was addressed. Both tumor antigens are highly and frequently expressed in the majority of carcinomas, including head and neck squamous cell carcinomas (HNSCC), and represent prognostic and therapeutic tumor target molecules. FITC‐conjugated EGF‐R‐ and EpCAM‐specific antibodies served as molecular tools for the detection of antigen‐positive cells using the CLE technology. Specificity of both antibodies and their ability to discriminate tumor from non‐tumor cells were assessed in vitro with human fibroblasts and PCI‐1 HNSCC cell lines, and ex vivo on primary HNSCC samples ( n = 11) and healthy mucosa ( n = 5). Antigen specificity of the used EpCAM‐specific antibody was superior to that of the EGF‐R‐specific antibody both in vitro and ex vivo (100% vs. 31.25%), and allowed visualization of cellular structures in CLE measurements. These results hold promise for possible future applications in humans. Abstract : Optimizing detection of resection margins during tumor surgery is a promising means to reduce local recurrence. Here, the use of antibodies specific for the tumor antigens EGF‐R and EpCAM as probes for confocal laser scanning endomicroscopy (CLE) was evaluated in vitro on permanent cell lines and ex vivo on HNSCC specimens and healthy mucosa. Both, EpCAM and EGF‐R are promising candidates for CLE‐mediated detection of residual carcinoma cells.Hypopharyngeal Carcinoma G3 p16‐, staining with EpCAM‐antibody (A) Histological slide, (B) corresponding examination with Confocal Laser Scanning Microscope, (C) pCLE image, () approximate depth of penetration with CLE